Bioprospection of above ground biomass from ashwagandha plant: A waste valorisation approach - Sarkar, Rohan; Basak, Biraj Bandhu; Das, Manish (Indian Horticulture, 2023)
The medicinal plant, Withania somnifera, commonly known as ashwagandha is mainly grown for the roots having several health promoting effects that is in conformity to the traditional knowledge of Indian system of medicine. But once the roots are harvested, the large amount of residual plant biomass (above ground part) remains unused. Studies suggest presence of various bioactive compounds in this plant biomass that can be transformed to several value-added products. This article primarily focuses on important bioactive compounds like plant secondary metabolites and dietary fibres, their content and how these compounds can be utilized further as an effective biorefinery that would be of im mense useful for the stakeholders i.e., industry as well as farmers. Fabrication of efficient technologies are the prime factor to utilize the residual biomass in an economical way that can be beneficial to industries and this will ultimately help to provide an assured market to the farmers to sell their produce. This article provides an insight regarding utilization of the residual biomass of Withania somnifera for its value addition towards higher economic return.